2013
DOI: 10.1155/2013/956312
|View full text |Cite
|
Sign up to set email alerts
|

System Consolidation of Spatial Memories in Mice: Effects of Enriched Environment

Abstract: Environmental enrichment (EE) is known to enhance learning and memory. Declarative memories are thought to undergo a first rapid and local consolidation process, followed by a prolonged process of system consolidation, which consist in a time-dependent gradual reorganization of brain regions supporting remote memory storage and crucial for the formation of enduring memories. At present, it is not known whether EE can affect the process of declarative memory system consolidation. We characterized the time cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 85 publications
7
20
2
Order By: Relevance
“…The authors suggest that enrichment causes a significant increase in hippocampal Ng levels. More recent research has demonstrated that an enriched environment may result in enhancing memory by accelerating the activity of the medial prefrontal cortex, which has a role in processing spatial memories, and results in the recruitment of additional cortical areas into the network sustaining spatial memories …”
Section: Effects Of Enrichmentmentioning
confidence: 99%
“…The authors suggest that enrichment causes a significant increase in hippocampal Ng levels. More recent research has demonstrated that an enriched environment may result in enhancing memory by accelerating the activity of the medial prefrontal cortex, which has a role in processing spatial memories, and results in the recruitment of additional cortical areas into the network sustaining spatial memories …”
Section: Effects Of Enrichmentmentioning
confidence: 99%
“…The benefits of enrichment are thought to arise from a combination of increased exercise, socialisation, and novelty, producing stronger effects than each of these components administered individually (Cracchiolo et al, 2007;Einon et al, 1980;Olson et al, 2006;Sozda et al, 2010;Will et al, 1986;Wood et al, 2001). These effects are likely to be mediated by increased activation of multiple brain networks, including changes to their recruitment during behavioural tasks, together with neurobiological effects that range from the size and morphology of brain regions to the survival and complexity of neurons, adult neurogenesis, enhanced cell excitability and synaptic plasticity, and a wide array of neuroprotective molecular responses that reflect multiple genetic processes, including neuroinflammation and levels of trophic factors (Alwis and Rajan, 2014; Bonaccorsi et al, 2013;Briones et al, 2013;Eckert and Abraham, 2013;Hirase and Q5 Shinohara, 2014;Leger et al, 2012;Rampon, 2000;Will et al, 2004).…”
Section: Environmental Enrichment and Recovery Of Function After Braimentioning
confidence: 99%
“…Discrepancies in c-Fos labeling in the hippocampus may result from different behavioural tasks used in assessment. Bonaccorsi et al (2013), Wartman and Holahan (2013), and Lopez et al (2012), used the water maze task as a behavioural measure and found increased activation of the hippocampus at remote compared to recent time points, consistent with the present set of results. Schlesiger et al (2013) used a modified radial arm maze task that incorporated different start locations and retention testing in a single trial in an effort to incorporate aspects of a standard water maze procedure.…”
Section: Discussionsupporting
confidence: 89%
“…Stereological analyses revealed remotely tested groups had significantly higher numbers of c-Fos positive cells than recently tested groups. This finding contradicts some earlier reports that revealed lower hippocampal activation at remote time points (Frankland et al, 2004;Maviel et al, 2004) but is similar to other reported data (Bonaccorsi et al, 2013;Lopez et al, 2012;Schlesiger et al, 2013;Wartman and Holahan, 2013). As the WM task is a hippocampal-dependent task, it comes as no surprise the hippocampus was activated during the probe test (Broadbent et al, 2006;Clark et al, 2005a,b;D'Hooge and De Deyn, 2001;Holahan and Routtenberg, 2011;Morris et al, 1986Morris et al, , 1982Ramos, 2009;Remondes and Schuman, 2004;Sutherland et al, 2001Sutherland et al, , 1983Teixeira et al, 2006;Wiltgen et al, 2010).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation